2011
DOI: 10.2190/ag.72.2.d
|View full text |Cite
|
Sign up to set email alerts
|

Proactive Coping in Community-Dwelling Older Australians

Abstract: This article reports on a study of older community-dwelling Australian adults which aimed to test whether a relatively unexplored construct, proactive coping, could have a role in purpose in life, personal growth, and life satisfaction. A total of 109 women and 115 men (Mean age = 75.04 yrs, SD = 6.66) completed a questionnaire containing Greenglass et al.'s (1999) Proactive Coping Inventory, the Purpose in Life and Personal Growth subscales of Ryff's (1989) Psychological Well-being Scales, and the Satisfactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 31 publications
3
25
0
Order By: Relevance
“…Purpose was also reported to predict faster recovery to prestress baseline levels following exposure to an acute social laboratory stressor (Fogelman & Canli, 2015) and lower incidence of sleep disturbance (E. S. Kim, Hershner, & Strecher, 2015). A cross-sectional study of older adults found that purpose had a significant and positive relationship with self-reported health, personal growth, proactive coping, and life satisfaction (Sougleris & Ranzijn, 2011). Higher scores for purpose was also associated with greater use of preventative health-care services and screening, increased frequency of physical activity (Holahan & Suzuki, 2006;Yu et al, 2015), and fewer nights of hospitalization (E. S. Kim, Strecher, & Ryff, 2014) Two studies explored the relationship of purpose with Alzheimer's disease (AD) and cognitive functioning for older adults.…”
Section: Purpose and Physical Outcomesmentioning
confidence: 99%
“…Purpose was also reported to predict faster recovery to prestress baseline levels following exposure to an acute social laboratory stressor (Fogelman & Canli, 2015) and lower incidence of sleep disturbance (E. S. Kim, Hershner, & Strecher, 2015). A cross-sectional study of older adults found that purpose had a significant and positive relationship with self-reported health, personal growth, proactive coping, and life satisfaction (Sougleris & Ranzijn, 2011). Higher scores for purpose was also associated with greater use of preventative health-care services and screening, increased frequency of physical activity (Holahan & Suzuki, 2006;Yu et al, 2015), and fewer nights of hospitalization (E. S. Kim, Strecher, & Ryff, 2014) Two studies explored the relationship of purpose with Alzheimer's disease (AD) and cognitive functioning for older adults.…”
Section: Purpose and Physical Outcomesmentioning
confidence: 99%
“…First, the psychological benefits of purpose in life may make care tasks less of a physical effort. In accord with this possibility, those with a stronger sense of purpose tend to have more energy and may be more adept at proactively coping with challenges [18][19][20][21]. Second, spousal caregivers with more purpose in life may take better care of their own health, which renders them better able to perform their care tasks.…”
Section: Discussionmentioning
confidence: 99%
“…First, we examined the links between spousal caregivers' and care recipients' feelings of purpose in life and caregivers' reports of emotional and physical difficulties from their care role. On the basis of theoretical and empirical work indicating the stress-buffering role of purpose in life (17)(18)(19)(20)(21) and that personal resources in the care dyad may affect caregivers' experience of care-related difficulties [43][44][45][46][47][48], we predicted the following:…”
Section: Study Aims and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Volunteers' identifi cation to the organization would aff ect the intention of continuous service. Volunteers have encountered several problems and trouble in the service process, such as competition among volunteers and bad communication between organization staff and volunteers, which would reduce volunteers' intention of continuous service (Ranzijn, 2011). Apparently, the egoistic and altruistic benefi ts in the voluntary service are the key of volunteers intending to continuously participate in voluntary service.…”
Section: Intention Of Continuous Participationmentioning
confidence: 99%